'Venus trapped, Mars transits': Cu and Fe redox chemistry, cellular topography and in situ ligand binding in terrestrial isopod hepatopancreas. Issue 3 (March 2016) - Kille, P.; Morgan, A. J.; Powell, K.; Mosselmans, J. F. W.; Hart, D.; Gunning, P.; Hayes, A.; Scarborough, D.; McDonald, I.; Charnock, J. M.
Abstract : Woodlice efficiently sequester copper (Cu) in 'cuprosomes' within hepatopancreatic 'S' cells. Binuclear 'B' cells in the hepatopancreas form iron (Fe) deposits; these cells apparently undergo an apocrine secretory diurnal cycle linked to nocturnal feeding. Synchrotron-based µ-focus X-ray spectroscopy undertaken on thin sections was used to characterize the ligands binding Cu and Fe in S and B cells of Oniscus asellus (Isopoda). Main findings were: (i) morphometry confirmed a diurnal B-cell apocrine cycle; (ii) X-ray fluorescence (XRF) mapping indicated that Cu was co-distributed with sulfur (mainly in S cells), and Fe was co-distributed with phosphate (mainly in B cells); (iii) XRF mapping revealed an intimate morphological relationship between the basal regions of adjacent S and B cells; (iv) molecular modelling and Fourier transform analyses indicated that Cu in the reduced Cu + state is mainly coordinated to thiol-rich ligands (Cu–S bond length 2.3 Å) in both cell types, while Fe in the oxidized Fe 3+ state is predominantly oxygen coordinated (estimated Fe–O bond length of approx. 2 Å), with an outer shell of Fe scatterers at approximately 3.05 Å; and (v) no significant differences occur in Cu or Fe speciation at key nodes in the apocrine cycle. Findings imply that S and B cells form integrated unit-pairs; a functional role for secretions from these cellular units in the digestion of recalcitrant dietary components is hypothesized.